HOW DOES GROUP DISCUSSION MINIMIZE ON TASK BEHAVIOR - Surti Nur Utami; Rina Wahyuni (UAD TEFL International Conference)
This research investigated the students learning behavior during the Reading class. The aimed of this study was improving students’ on-task behavior using group discussion. Furthermore, this study reveals the students’ attitudes who mostly were not directing their eyes gaze at the teacher and the instructional activity. For instance, the students did not pay attention toward appropriate instructional material and they were looking elsewhere. Thus, that behave was classified as off-task. While On-task behavior was defined as activity that complied with instructions given by the teacher for that lesson. Based on the previous matter, the use of group discussion during the classroom activities is definitely a fascinating phenomenon that can improve their on-task behavior during the learning activities in the class, especially reading.